Burkina Faso : Fourth Review Under the Poverty Reduction and Growth Facility and the Third Annual Program. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines Burkina Faso's Fourth Review Under the Poverty Reduction and Growth Facility (PRGF) and the Third Annual Program. The program remains broadly on track. The economic downturn of 2000 trailed into the first half of 2001. All of the end-June and end-September 2001 quantitative and structural performance criteria, benchmarks, and indicators were met, except for the indicator on current government revenue. Real GDP for 2001 is projected to grow by 6.2 percent on the basis of a rebound in agricultural output.